Photoshop CS4. - Weinmann, Elaine (Visual quickstart guide., 2009)
This full-color Visual QuickStart Guide is a more advanced companion volume to the best-selling Photoshop CS4 Visual QuickStart Guide from the same authors. This book takes designers and photographers beyond the basics with more focused tasks that are written in greater depth. For instructors this Visual QuickStart guide provides more advanced tutorials for students who need to master Photoshop, and can be a real time-saver for developing curriculum. Best-selling authors Elaine Weinmann and Peter Lourekas cover many key areas in Photoshop, including: methods for creating complex selections; specific steps to improve tone and color; in-depth tasks for retouching portraits; a closer look at combining images into composites; thorough coverage of Camera Raw 5.2; detailed steps for improving sharpening; creative use of tinting; applying fine art touches to an image; and steps for creative type treatments.